Pengaruh Konseling Kelompok Pendekatan Rational Emotive Behavior Therapy untuk Mengurangi Insecurity pada siswa yang mengalami Body Shaming Di SMP - Dea Istikomah; Anni Suprapti; Adif Jawadi Saputra (Consilia : Jurnal Ilmiah Bimbingan dan Konseling, 2025)
Abstract This study aimed to examine the effect of group counseling services using the Rational Emotive Behavior Therapy (REBT) approach in reducing the level of insecurity among students who experienced body shaming at the junior high school level. The research employed an experimental method with a two-group pre-test post-test design. The population consisted of 71 students, and the sample included 10 students selected using purposive sampling. Data were collected through an insecurity questionnaire based on a Likert scale, and analyzed using a t-test. The t-test results showed a significant difference in insecurity levels before and after the intervention, indicating that group counseling with the REBT approach had an effect in reducing students’ insecurity. Future research is recommended to use a larger sample to improve the generalizability of the findings. Keywords: insecurity, group counseling, rational emotive behaviour therapy approach